Pengaruh Metode Pembelajaran Praktek Kultum Terhadap Hasil Belajar Siswa pada Mata Pelajaran Aqidah Akhlak di Madrasah Aliyah Muhammadiyah Sei Apung Jaya - Wal’adiati, Wal’adiati; Setiawan, Hasrian Rudi (LP. Ma'arif Janggan Magetan, 2024)
The purpose of this study was to determine the effect of the use of the cultum practice learning method on student learning outcomes in the subject of aqidah akhlak. The research method used in this study is a quantitative method. This study has a population of 39 people. With a sample of 39 students, the data collection technique in this study used a pre-test and post-test. Based on the results of statistical calculations, this study has a positive relationship between the effect of cultum practice and student learning outcomes in the subject of aqidah akhlak at the Muhammadiyah Sei Apung Jaya Islamic High School.